SISTEM KOMUNIKASI PENGEMBANGAN PANGAN LOKAL DI PROVINSI MALUKU (KASUS PANGAN LOKAL ENBAL DI KABUPATEN MALUKU TENGGARA) - Risyart Alberth Far Far; Lydia Maria Ivakdalam; George S J Tomatala (Pattimura University, 2022)
The people of Southeast Maluku Regency process bitter cassava as household food which is known as